Mechanotransduction and Uterine Blood Flow in Preeclampsia: The Role of Mechanosensing Piezo 1 Ion Channels. (23rd September 2019) - Arishe, Olufunke O; Ebeigbe, Anthony B; Webb, R Clinton
Abstract: There is a large increase in uterine arterial blood flow during normal pregnancy. Structural and cellular adjustments occur in the uterine vasculature during pregnancy to accommodate this increased blood flow through a complex adaptive process that is dependent on multiple coordinated and interactive influences and this process is known as "vascular remodeling." The etiology of preeclampsia involves aberrant placentation and vascular remodeling leading to reduced uteroplacental perfusion. The placental ischemia leads to development of hypertension and proteinuria in the mother, intrauterine growth restriction, and perinatal death in the fetus. However, the underlying source of the deficient vascular remodeling and the subsequent development of preeclampsia remain to be fully understood. Mechanoreceptors in the vascular system convert mechanical force (shear stress) to biochemical signals and feedback mechanisms. This review focuses on the Piezo 1 channel, a mechanosensitive channel that is sensitive to shear stress in the endothelium; it induces Ca 2+ entry which is linked to endothelial nitric oxide synthase (eNOS) activation as the mechanoreceptor responsible for uterine vascular dilatation during pregnancy. Here we describe the downstream signaling pathways involved in this process and the possibility of a deficiency in expression of Piezo 1 in preeclampsia leading to the abnormal vascular dysfunction responsible for the pathophysiology of the disease. The Piezo 1 ion channel is expressed in the endothelium and vascular smooth muscle cells (VSMCs) of small-diameter arteries. It plays a role in the structural remodeling of arteries and is involved in mechanotransduction of hemodynamic shear stress by endothelial cells (ECs).